Forskolin Stimulates Estrogen Receptor (ER) α Transcriptional Activity and Protects ER from Degradation by Distinct Mechanisms - Houng-Wei Tsai; Vicky Y. Lin; Margaret A. Shupnik (International Journal of Endocrinology)
Estradiol action is mediated by estrogen receptors (ERs), a and ß. Estradiol binding initiates ER-mediated transcription and ER degradation, the latter of which occurs via the ubiquitin-proteasome pathway. Inhibition of proteasome activity prevents estradiol-induced ERα degradation and transactivation. In ER-positive GH3 cells (a rat pituitary prolactinoma cell line), forskolin, acting via protein kinase A (PKA), stimulates ERα transcriptional activity without causing degradation, and proteasome inhibition does not block forskolin-stimulated transcription. Forskolin also protects liganded ERα from degradation. In the current study, we first examined ERα and ERβ transcriptional activity in ER-negative HT22 cells and found that forskolin stimulated ERα-, but not ERβ-dependent transcription, through the ligand-binding domain (LBD). We also identified four mutations (L396R, D431Y, Y542F, and K534E/M548V) on the ERα LBD that selectively obliterated the response to forskolin. In GH3 cells, transfected ERα mutants and ERβ were protected from degradation by forskolin. Ubiquitination of ERα and ERβ was increased by forskolin or estradiol. ERα ubiquitination was diminished by a mutated ubiquitin (K48R) that prevents elongation of polyubiquitin chains for targeting the proteasome. Increased ERα ubiquitination was not affected by the deletion of the A/B domain but significantly diminished in the F domain deletion mutant. Our results indicate distinct and novel mechanisms for forskolin stimulation of ERα transcriptional activity and protection from ligand-induced degradation. It also suggests a unique mechanism by which forskolin increases unliganded and liganded ERα and ERβ ubiquitination but uncouples them from proteasome-mediated degradation regardless of their transcriptional responses to forskolin.